Pengaruh perlakuan cekaman kekeringan terhadap pertumbuhan semai cempaka wasian, nantu, dan mahoni - Irawan, Arif; Hidayah, Hanif Nurul; Mindawati, Nina (Jurnal Penelitian Kehutanan Wallacea, 2019)
Climate change has shortened the rainy season compared to the dry season in North Sulawesi. The El Nino phenomenon occurred in 2015 had an impact on the death of clove plants due to drought. Drought stress testing on several types of forestry plants in the North Sulawesi area is a matter that needs to be done in line with these conditions. Development of cempaka wasian (Magnolia tsiampaca (Miq.) Dandy), nantu (Palaquium obtusifoliumBurck), and mahoni (Swietenia macrophylla King) plantations have been carried out by communities in North Sulawesi for a long time and have very good prospects. The research was done by conducting a simulation test at seedling level with treatment to be tested on volume and interval of watering. The watering volume consists of 3 levels, i.e.100%, 50%, and 25% watering of the field capacity, while the watering intervals included once-daily, 3-day and 5-day watering once for 18 weeks. The results showed that nantu species has better resistance to drought stress conditions compared with mahogany and cempaka wasian.